Maternal Glutaric Acidemia, Type I Identified by Newborn Screening - Crombez, Eric A. (2008)
We report two women with glutaric acidemia type I in whom the diagnosis was unsuspected until a low carnitine level was found in their newborn children. Both mothers had low carnitine in plasma. In the first, organic acid analysis was only done after fibroblast studies revealed normal carnitine uptake. Having learned from the first family, organic acid analysis was done immediately in the mother of family 2. In both, the plasma acylcarnitine profile was normal but both excreted the metabolites typical of their disorder. One of the women was a compound heterozygote for distinct mutations in the glutaric acid dehydrogenase gene, whereas the second was either homozygous or hemizygous for a mutation in Exon 6 of the gene.